Case of primary Sjogren's syndrome preceded by dystonia. (4th June 2018) - Ararat, Kerime; Berrios, Idanis; Hannoun, Anas; Ionete, Carolina
Abstract : There are only six cases in literature that describe development of dystonia with Sjogren's syndrome (SS). We describe a case of a 43-year-old woman who presented with symptoms including movement disorder, sensory neurogenic bladder, sensory loss and neuropathic pain, migraine like headaches, musculoskeletal pain, Raynaud's phenomenon and dysautonomia. Symptoms started in 2000, with weakness that progressed to dystonia in 2003. Diagnostic work-up was inconclusive with negative inflammatory serologies, cerebrospinal fluid and MRI for many years. After patient developed sicca syndrome with dry eyes and mouth in 2009, her rheumatoid factor titre was elevated (550 IU/mL), erythrocyte sedimentation rate, anti-Sjogrens syndrome-related antigen A (anti-Ro/SSA) and anti-SSB/La: anti-Sjogrens syndrome-related antigen B (anti-La/SSB) became positive. Lip biopsy confirmed diagnosis of SS. She was diagnosed with primary SS with neurological involvement. Her symptoms responded well to intravenous methylprednisolone. Symptoms stabilised with trials of immune-suppressive therapy. This is a case that demonstrates the delay of diagnosing SS with preceding unique neurological association.